Automation psychological assessments with cloud computing - Ubalde Enriquez, Rembrandt (2020)
This paper deals with the automation of psychological assessments to help to select the right candidate for the organization during the recruitment process on a human resources consulting firm. The solution was developed with Kanban Method and cloud computing, such as Amazon Web Services (AWS), where it was integrated and launched with other services to improve security and operativity. Experiments were divided into functionalities: (1) an interface for mobile phones and (2) notifying recruiter by SMS and Email when candidate finalize the tests. The results show improved recruiter response time to analyze test results and prepare psychological reports in two and a half months. The recruiter's performance increased by up to 5% in person-hours.